Scaffolding: A Process of Transforming Patterns of Inequality in Small-Scale Societies - Mair, Johanna; Wolf, Miriam; Seelos, Christian (Academy of Management Journal, 2016)
This study advances research on organizational efforts to tackle multidimensional, complex, and interlinked societal challenges. We examine how social inequality manifests in small-scale societies, and illustrate how it inheres in entrenched patterns of behavior and interaction. Asking how development programs can be organizing tools to transform these patterns of inequality, we use a program sponsored by an Indian non-governmental organization as our empirical window and leverage data that we collected over a decade. We identify “scaffolding” as a process that enables and organizes the transformation of behavior and interaction patterns. Three interrelated mechanisms make the transformation processes adaptive and emerging alternative social orders robust: (1) mobilizing institutional, social organizational, and economic resources; (2) stabilizing new patterns of interaction that reflect an alternative social order; and (3) concealing goals that are neither anticipated nor desired by some groups. Through this analysis, we move beyond conventional thinking on unintended consequences proposed in classic studies on organizations, complement contemporary research about how organizations effect positive social change by pursuing multiple goals, and develop portable insights for organizational efforts in tackling inequality. This study provides a first link between the study of organizational efforts to alleviate social problems and the transformation of social systems.